Missile embolism from pulmonary vein to left ventricle: report of a case - Khorgami, Mohammadrafie; Khalaj, Fattaneh; Gholampour, Maziar; Tatari, Hassan (Frontiers in Cardiovascular Medicine, 2024)
Missile embolization is rare in penetrating trauma, occurring in 0.3% of cases. Bullet embolism into the left ventricle is less frequent, with few instances described in the literature. This paper describes an instance of left ventricular bullet embolism from the pulmonary venous system following gunshot chest trauma. A 7-year-old boy sustained a gunshot wound to his chest during an assault accident. Despite thoracic pain, he remained conscious and exhibited vital signs. A CXR and CT scan revealed a bullet in the left mediastinum. A left thoracotomy was performed to remove blood and clots from the pericardium. The patient was sent to a tertiary referral hospital for further investigation. The patient underwent elective surgery to remove the foreign body from inside the heart. The procedure involved a partial thymectomy and pericardial opening, and the patient was released from medical care after 14 days. After 6 months, there were no signs or symptoms of cardiothoracic infection or evidence of mitral valve regurgitation in echocardiography.